Characterization of the RNA-interference pathway as a tool for reverse genetic analysis in the nascent phototrophic endosymbiosis, Paramecium bursaria. Issue 4 (21st April 2021) - Jenkins, Benjamin H.; Maguire, Finlay; Leonard, Guy; Eaton, Joshua D.; West, Steven; Housden, Benjamin E.; Milner, David S.; Richards, Thomas A.
Abstract : Endosymbiosis was fundamental for the evolution of eukaryotic complexity. Endosymbiotic interactions can be dissected through forward- and reverse-genetic experiments, such as RNA-interference (RNAi). However, distinguishing small (s)RNA pathways in a eukaryote–eukaryote endosymbiotic interaction is challenging. Here, we investigate the repertoire of RNAi pathway protein-encoding genes in the model nascent endosymbiotic system, Paramecium bursaria–Chlorella spp. Using comparative genomics and transcriptomics supported by phylogenetics, we identify essential proteome components of the small interfering (si)RNA, scan (scn)RNA and internal eliminated sequence (ies)RNA pathways. Our analyses reveal that copies of these components have been retained throughout successive whole genome duplication (WGD) events in the Paramecium clade. We validate feeding-induced siRNA-based RNAi in P. bursaria via knock-down of the splicing factor, u2af1, which we show to be crucial to host growth. Finally, using simultaneous knock-down 'paradox' controls to rescue the effect of u2af1 knock-down, we demonstrate that feeding-induced RNAi in P. bursaria is dependent upon a core pathway of host-encoded Dcr1, Piwi and Pds1 components. Our experiments confirm the presence of a functional, host-derived RNAi pathway in P. bursaria that generates 23-nt siRNA, validating the use of the P. bursaria – Chlorella spp. system to investigate the genetic basis of a nascent endosymbiosis.